2018
DOI: 10.11157/fohpe.v19i3.217
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ experience of a Teddy Bear Hospital as part of a paediatric curriculum

Abstract: Introduction: Teddy Bear Hospital is a strategy used to help reduce children's fears of the healthcare system and teach them about health-related issues. It involves mock consultations where medical students play the role of a "teddy doctor" and children act as the carer of teddy, or another soft toy, requiring consultation. This provides medical students with the opportunity to interact with children and develop communication skills while children are introduced to the medical consultation process. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…1,2 Previous qualitative studies suggest that TBHP increases volunteers' comfort interacting with children, prepares children for uncomfortable procedures, and improves history-taking from pediatric patients. 3,4 However, no study has demonstrated its effect on volunteers' comfort communicating medical concepts to children, an important skill to acquire for students hoping to pursue a career with a large proportion of pediatric patients (i.e. family medicine or pediatrics).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Previous qualitative studies suggest that TBHP increases volunteers' comfort interacting with children, prepares children for uncomfortable procedures, and improves history-taking from pediatric patients. 3,4 However, no study has demonstrated its effect on volunteers' comfort communicating medical concepts to children, an important skill to acquire for students hoping to pursue a career with a large proportion of pediatric patients (i.e. family medicine or pediatrics).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the studies claims that some children were not as attentive during lectures or information as far as conveying medical information [21]. This only proves that the health care students who participate in this program should work on their communication skills, especially when it comes to verbalizing patient data to children aged 4-12 years old, as their mindset cannot yet comprehend the numerous ramifications lying within it [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that regardless of the different approaches and strategies used to implement the Teddy Bear Hospital, they all ultimately share the same intent: to raise health care awareness and alleviate young children's anxiety over medical treatment while focusing on the promotion of positive healthy lifestyle. Of the 11 included studies, 2 were quasi-experimental pre/post design [13], [16], 1 scoping systematic review [17], 2 were Analysis of variance ANOVA [7], [19], 1 control group trials [8] and the remainder were qualitative research studies [11], [12], [14], [15], [18].…”
Section: Objectives and Approaches Taken In Conducting The Teddy Bear Hospitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Teddy Bear Hospital (TBH) is a university student-led volunteering group present in many universities and medical schools internationally [1][2][3][4][5]. It utilises play to promote healthy living among primary school children (aged 5 to 7 years) and reduce their anxiety surrounding hospitals and healthcare professionals [6].…”
Section: Introductionmentioning
confidence: 99%